DINAMIKA COPING STRESS BURUH PABRIK ROKOK WANITA YANG SUDAH BERKELUARGA DI KABUPATEN KUDUS - Sari, Niken Mulia; Lestari, Eva; Sary, Etrya Loralita Mella; Hakim, Mohamad Lutfi; Khasan, Mohammad (Jurnal Psikohumanika, 2024)
Having status a woman who works outside the home and as a housewife, makes it a challenge for factory workers because they have to carry out two roles at once. Purpose this study to determine the coping process carried out, the sources of stress, and the types of stress coping used by married female cigarette factory workers, especially in Kudus district. This research uses qualitative research with a phenomenological approach with 12 informants with the criteria 1) female cigarette factory workers, 2) domiciled in Kudus Regency, 3) married, and 4) already have children. Research instrument uses cigarette workers' cores including interview and observation guides that have been registered in the Ministry of Law and Human Rights manufacturing registration letter number EC00202384255 with coding data analysis, research credibility using triangulation of data sources and experts. The results showed that there are several sources of stress, including work problems scolded by superiors, lack of materials, arguing with coworkers, long work, work tool problems. Problems at home such as problems with children, husband, in-laws, economic problems, problems with relatives, taking care of the house, and not being able to divide time. Types of coping used are emotion focused coping and problem focused coping.